Kajian Literatur: Aktivitas Antioksidan Ekstrak Tanaman Cempedak (Artocarpus champeden Spreng): Literature Review: Antioxidant Activity of Cempedak Plant Extract (Artocarpus champeden Spreng) - Aulia Alfath Rahmawati; Mirhansyah Ardana; Yurika Sastyarina (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2021)
Antioxidants are compounds that can counteract free radicals. One of the plants that have antioxidant activity is cempedak, because cempedak contains flavonoids compounds. This writing aims to determine the antioxidant activity of cempedak plants based on a review of several literatures. The method of writing a literature review uses a journal search from Google Scholar. Based on the literature review that has been carried out, the leaves and bark of cempedak have antioxidant activity. Based on the literature review of antioxidant activity of cempedak, methanol extract of stem bark had antioxidant activity of 100,26 ppm, leaf methanol extract 8,88 ppm, leaf ethanol extract 52,7706 ppm, leaf ethyl acetate fraction 4,282 ppm. The part of the cempedak plant that has the highest antioxidant activity is found in the leaves with the ethyl acetate fraction which shows an IC50 value of 4,282 ppm. Based on the IC50 value obtained, the ethyl acetate fraction of cempedak leaves has a very strong antioxidant activity because the IC50 is below 50 ppm.